2019
DOI: 10.1007/s12355-019-00754-5
|View full text |Cite
|
Sign up to set email alerts
|

Various Methods of Assessing Sugar Beet Seed Vigour and Its Impact on the Germination Process, Field Emergence and Sugar Yield

Abstract: During 2012-2015, the seed vigour of 54 commercial sugar beet varieties was evaluated. In addition, correlations among different methods of determining seed vigour and the potential impact of low vigour on the quality traits of seeds and root yield were investigated. The chosen seed vigour indicators were field emergence (early and final count), emergence course in a phytotron under controlled conditions (early and final count, mean time of emergence, emergence uniformity) and germination ability under stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These findings are supported by Ronga et al [ 25 ], who found that a two-fold concentration (around 25 mgC org /L) of an aqueous C. vulgaris microalgal extract did not show phytotoxicity effect, by measuring the GI index, on a sensitive species to phytotoxic compounds such as cress. Interestingly, from a physiological point of view, several authors [ 29 , 30 , 31 , 32 ] have reported that the faster emergence in sugar beet showed an enormous influence on plant characteristics, showing a higher dry matter weight compared to the plants emerging later. Among these authors, Podlaski et al [ 32 ] demonstrated that the time of emergence was the strongest factor influencing plant weight in sugar beet during harvest season.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are supported by Ronga et al [ 25 ], who found that a two-fold concentration (around 25 mgC org /L) of an aqueous C. vulgaris microalgal extract did not show phytotoxicity effect, by measuring the GI index, on a sensitive species to phytotoxic compounds such as cress. Interestingly, from a physiological point of view, several authors [ 29 , 30 , 31 , 32 ] have reported that the faster emergence in sugar beet showed an enormous influence on plant characteristics, showing a higher dry matter weight compared to the plants emerging later. Among these authors, Podlaski et al [ 32 ] demonstrated that the time of emergence was the strongest factor influencing plant weight in sugar beet during harvest season.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, from a physiological point of view, several authors [ 29 , 30 , 31 , 32 ] have reported that the faster emergence in sugar beet showed an enormous influence on plant characteristics, showing a higher dry matter weight compared to the plants emerging later. Among these authors, Podlaski et al [ 32 ] demonstrated that the time of emergence was the strongest factor influencing plant weight in sugar beet during harvest season.…”
Section: Resultsmentioning
confidence: 99%
“…Seeds with high germination energy typically also have higher seedling vigor and dry matter weight, as well as enhanced stress tolerance to both abiotic and biotic stresses, including fungal pathogens [ 38 ]. The germination index is an indicator of seed vigor under stress conditions, and a higher germination index indicates a higher number of vigorous seeds.…”
Section: Resultsmentioning
confidence: 99%
“…They alsoincreased the seedling root and shoot length as well as the amylase activity of seedlings at 5 days after sowing compared with the control (rice seeds not treated with pectic-oligosaccharides). Seeds with high germination energy typically also have higher seedling vigor and dry matter weight, as well as enhanced stress tolerance to both abiotic and biotic stresses, including fungal pathogens [38]. The germination index is an indicator of seed vigor under stress conditions, and a higher germination index indicates a higher number of vigorous seeds.…”
Section: Effect Of Ogs On Sugar Beet Seed Germinationmentioning
confidence: 99%
“…In fact, it was stronger than such factors as the average weight of neighbouring plants or mean distance to neighbouring plants. Podlaski and Chomontowski (2020) proposed that variability in the root yield from different plantations cultivating the same plant cultivar and comparable population grown under comparable agro-ecological conditions stemmed from the spread in the rate and uniformity of plant emergences. These differences disappear with the progress of crop development; their effect lasts towards the harvest, nonetheless.…”
Section: Resultsmentioning
confidence: 99%